Profiling an Ideal Teacher - Rianti, Ade; Hidayati, Arini Nurul; Pertamana, Dede; Andriani, Agis; Abdullah, Fuad (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2020)
The article presents the perceptions of Indonesian vocational high school students in defining an ideal teacher; what makes a teacher good and bad. This qualitative study employs in-depth interviews to obtain the data. The findings informed that an ideal teacher is the one who builds a positive relationship with the students, for instance, having an individual consideration, easy going, having a deep empathy, motivating, performing comprehensible teaching, enthusiastic, humorous, assertive, humble and patient. Moreover, this type of teacher will also be far from being injustice, antipathy, irresponsible, authoritarian, and short-tempered. Some pedagogical implications areimplicitly discussed.